Erosive Pustular Dermatosis and Amivantamab for Lung Cancer: A Case Report - Senterre, Yseult; Bouillenne, Amandine; Sabatiello, Murielle; Demoulin, Anne-Sophie; Nikkels, Arjen F. (Case reports in dermatology, 2025)
Introduction: Amivantamab is a monoclonal antibody against EGFR and MET receptors, indications for certain types of non-small cell lung cancer. Due to its mechanisms, cutaneous adverse effects are frequent and numerous. Case Presentation: A 67-year-old woman with metastatic adenosquamous carcinoma, stage T3N2M1c, was treated with amivantamab after the first-line chemotherapy failed. Despite prophylactic oral tetracyclines, she developed severe erosive pustular dermatosis (EPD) affecting more than 50% of her scalp, forcing to cut short her hair to provide adequate local care. Conclusion: EPD is an exceptional and severe adverse event of amivantamab, requiring oral steroids, tetracyclines and appropriate local care with antibiotic creams. Clinicians should be aware of this complication as early therapeutic intervention is mandatory to avoid deleterious consequences and spontaneous recurrences.